“My Pronouns Are”: Pronoun-face mismatch performance and self-report attitudes to gender categorizaton across generations - Melissa Allen; Catherine Hobbs; Will Mills; Stephen Hinde; Bruce Hood (PLoS ONE, 2026)
Gender attribution based on face categorization may undergo age-related changes. Specifically, older individuals with more exposure to faces may have stronger stereotypical representations which leads to more automatic categorization. Investigating automatic binary pronoun assignment (he/she) allows us to examine whether older adults show greater categorical interference, with slower responses when pronouns do not match stereotypical faces. We tested this proposal by presenting individuals (N = 600: age range = 18–69 yrs) with a pronoun–face congruence task contrasting stereotypical faces with either congruent or incongruent binary (he/she) pronouns. Individuals also reported their explicit attitudes to preferred gender pronoun use with older individuals expressing more negative attitudes towards pronoun categorization as well as greater difficulty, but fewer worries than younger participants. Although older participants were overall slower, importantly, there were no age differences in pronoun–face interference. These findings support an age difference in explicit attitudes towards gender pronoun categorization that are not mirrored in reaction time measures.